Next Stop: Job! - Vanessa Spero-Swingle (EDIS)
Next Stop: Job is a multi-lesson program designed to teach youth, ages 14 and up, the skills necessary to obtain a job. Through videos and hands-on activities, youth learn essential job market skills, such as marketing, communication, writing skills, and financial literacy, to help them succeed in the workplace. This 28-page publication discusses cover letters, resumes, interviews, proper attire, and management of earnings. Written by Vanessa Spero-Swingle, Laura Cash, Laura Valencia, Gayle Whitworth, Karen Miliffe, and Shane Michael, and published by the UF 4-H Youth Development Department, June 2017.